Evaluation of lignan-loaded poly(ε-caprolactone) nanoparticles: synthesis, characterization, in vivo and in silico schistosomicidal activity - Lima, Thais C.; Magalhães, Lizandra G.; Paula, Lucas A. de L.; Cunha, Wilson R.; Januário, Ana H.; Pauletti, Patricia M.; Bastos, Jairo K.; dos Santos, Fransergio F.; Forim, Moacir R.; Laurentiz, Rosangela S. [UNESP]; Santos, Fernanda A. [UNESP]; Orenha, Renato P.; et al. (Taylor & Francis, 2021)
Lignan dinitrohinokinin displays important biological activities, which led to the preparation of its poly-ε-caprolactone nanoparticles. Kinetics analysis revealed initially slow drug release followed by a prolonged, moderate release 6 h later due to DNHK diffusion through the polymeric matrix. Molecular dynamics simulations show that DNHK molecules that interact stronger with other DNHK molecules near the PCL/DNHK surface are more difficult to dissociate from the nanoparticle. The smaller diameter nanocapsules with negative surface charge conferred good colloidal stability. The formulations showed a size distribution with monodisperse systems formation. In vivo evaluation of schistosomicidal activity against Schistosoma mansoni showed that DNHK, when incorporated into nanoparticles, caused egg number reduction of 4.2% and 28.1% at 40 mg/kg and 94.2% and 84.4% at 400 mg/kg in the liver and the spleen, respectively. The PCL nanoparticles were stable in aqueous dispersion and could be optimized to be used as a promising lignan release agent.
Keywords: (−)-6,6’-dinitrohinokinin (DNHK); anti-inflammatory activity; polymeric nanoparticles; schistosomicidal activity